Do stringent environmental policies and business regulations matter for economic growth? Evidence from G7 and BRICS economies - (:unkn) unknown (My University, 2022)
The environment has received particular concern since the 1950s when countries began to experience the negative impacts of environmental degradation. This study employs cointegration and causality analyses to explore the influence of stringent environmental policies and business regulations on economic growth between 2000 and 2015 in the Group of Seven and BRICS economies. The causality analysis shows that business regulations have a significant effect on economic growth in the short run, while stringent environmental policies have no significant effects during that time. The cointegration analysis, however, reveals a mixed interaction among stringent environmental policies, business regulations, and economic growth depending country specific characteristics.
Keywords: Tarımsal Bilimler; Çevre Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Environmental Engineering; Engineering and Technology; ÇEVRE BİLİMLERİ; Çevre / Ekoloji; Tarım ve Çevre Bilimleri (AGE); ENVIRONMENTAL SCIENCES; ENVIRONMENT/ECOLOGY; Agriculture & Environment Sciences (AGE); Doğa ve Peyzaj Koruma; Çevre Bilimi (çeşitli); Su Bilimi; Fizik Bilimleri; Yaşam Bilimleri; Nature and Landscape Conservation; Environmental Science (miscellaneous); Aquatic Science; Physical Sciences; Life Sciences; stringent environmental policies; business regulations; economic growth; panel cointegration; analysis; panel causality analysis; CARBON-DIOXIDE EMISSIONS; PORTER HYPOTHESIS; INNOVATION; IMPACT; COMPETITIVENESS; COINTEGRATION; PRODUCTIVITY; POLLUTION; AMERICA; PANELS